Species richness, conservation status, and potential uses of plants in Segara Anakan Area of Sempu Island, East Java, Indonesia - SITI NURFADILAH; LIA HAPSARI; ILHAM KURNIA ABYWIJAYA (Biodiversitas Journal of Biological Diversity, 2017)
Nurfadilah S, Hapsari L, Abywijaya IK. 2017. Species richness, conservation status, and potential uses of plants in Segara Anakan Area of Sempu Island, East Java, Indonesia. Biodiversitas 18: 1568-1588. Sempu Island is a small Island in Indonesia that has an important functional role as a nature reserve to protect unique landscapes and high plant species richness. Within the Island, one of the most frequently visited areas, Segara Anakan, needs careful attention in order to conserve its plant diversity. The objectives of the present study were to investigate the species richness, conservation status, and potential uses of plants in Segara Anakan, Sempu Island. The aim was to support management of the area and to reveal plants that have potential to be developed for useful products. A total of 77 plant species belonging to 43 families were recorded within the study area. These consisted of trees (55.84 %), shrubs (33.77%), herbs (9.09%) and epiphytes (1.3%). Two species were listed in the IUCN Red List as endangered (Cycas circinalis L. and Myristica teijsmannii Miq.). Plant species in Segara Anakan have many potential uses; namely for staple food, fruits, vegetables, flavouring, beverages, herbal medicines, timbers, ornamental plants, natural dyes, and other uses. The study has implications for biodiversity conservation and management of Sempu Island. Plant species on the IUCN Red List should receive priority in conservation efforts. Data concerning the potential uses of plants can serve as a basis for biodiversity conservation on Sempu Island.